2001
DOI: 10.1002/ajh.1159
|View full text |Cite
|
Sign up to set email alerts
|

TEL/AML1 rearrangement and the prognostic significance in childhood acute lymphoblastic leukemia in Hong Kong

Abstract: The TEL/AML1 rearrangement has been implicated as an independent good prognostic factor in pediatric acute lymphoblastic leukemia (ALL). We examined TEL/AML1 using nested reverse-transcription polymerase chain reaction (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
6
32
1
1
Order By: Relevance
“…21,22,32,40,41 The 25% incidence rate of TEL/AML1 þ cases in our study is in the upper range of the 18-26% reported in RT-PCR screening surveys. [3][4][5][6][9][10][11][12][13] In line with most of these reports, patients included in our analysis also presented with well-known good prognostic features at initial diagnosis. However, the prognostic relevance of TEL/AML1 itself is still controversial and though the majority of therapy studies still reports on an extraordinary good prognosis of TEL/AML1 þ patients, interestingly, those trials with large sample sizes and an adequate long-term follow-up found similar incidence rates of TEL/AML1 þ cases at initial diagnosis and relapse.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…21,22,32,40,41 The 25% incidence rate of TEL/AML1 þ cases in our study is in the upper range of the 18-26% reported in RT-PCR screening surveys. [3][4][5][6][9][10][11][12][13] In line with most of these reports, patients included in our analysis also presented with well-known good prognostic features at initial diagnosis. However, the prognostic relevance of TEL/AML1 itself is still controversial and though the majority of therapy studies still reports on an extraordinary good prognosis of TEL/AML1 þ patients, interestingly, those trials with large sample sizes and an adequate long-term follow-up found similar incidence rates of TEL/AML1 þ cases at initial diagnosis and relapse.…”
Section: Discussionsupporting
confidence: 60%
“…However, the prognostic relevance of TEL/AML1 itself is still controversial and though the majority of therapy studies still reports on an extraordinary good prognosis of TEL/AML1 þ patients, interestingly, those trials with large sample sizes and an adequate long-term follow-up found similar incidence rates of TEL/AML1 þ cases at initial diagnosis and relapse. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] We showed that with an excellent 90% 5-year EFS estimate, TEL/AML1 þ patients fared significantly better than TEL/AML1À patients, and that with an incidence of 14% among the relapsed BCP ALL study population, the prevalence rate of TEL/AML1 was clearly inferior as compared to the time point of primary diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have analyzed the clinical and biological features in ALL patients carrying the translocation t(12;21) leading to the TEL-AML1 gene fusion. [27][28][29][30][31][32][33][34][35][36][37][38] None of those studies reported a low Hb level to be associated with TEL-AML1. One study addressed this issue, but failed to demonstrate a correlation between Hb and TEL-AML1, probably due to the limited number of patients analyzed (11/51 patients TEL-AML1 + ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, global frequency of TEL-AML1 positivity has been reported to be 20-30% in pediatric ALL (Hong et al, 2008), some authors have reported very lower frequencies of TEL-AML1in some geographical regions (Kwong and Wong, 1997;Eguchi-Ishimae et al, 1998;Garcia-Sanz et al, 1999;Tsang et al, 2001;Rahman et al, 2006;Chung et al, 2010;Mazloumi et al, 2012) including one study from a single centre at Lahore, Punjab, Pakistan indicating 6% (3/50) frequency of TEL-AML1 (Faiz and Qazi, 2010), while others have reported frequency of this gene to be at other single Centres to be about 16% (Iqbal et al, 2007;Sabir et al, 2012). However, all of these studies were carried out at single centre or locations in Pakistan and therefore does not provide a comprehensive view of TEL-AML1 frequency in Pakistani population.…”
Section: Molecular Genetic Studies On 167 Pediatric All Patients Frommentioning
confidence: 99%